KEBERADAAN BUMDES SEBAGAI PENGGERAK EKONOMI MASYARAKAT - Ika Fitriyani; Muhammad Nur Fietroh (JURNAL CAFETARIA, 2023)
This study aims to determine the existence of BUMDes in Ranan Village, Ropang District as a driving force for the community's economy. This research is an inductive qualitative research, namely analysis based on data obtained from interviews, field notes and library materials. The data analysis technique used is data reduction, data presentation, and conclusion/verification. The results of his research concluded that improving the economy through BUMDes Ranan had provided a good role for the economy of the village community. With the existence of a capital loan business unit at BUMDes, the community can borrow from BUMDes, but it is necessary to improve financial governance in the field of savings and loans so that customers make loans with a fast process and lower interest. Community participation, optimal human resource competence and quality management are the strategies for managing BUMDes to be better than before. Even though bad credit still occurs in the savings and loan business, the method taken is through improving the scheduling and requirements for returning loans to customers as well as by restructuring credit to become a facility for achieving BUMDes Ranan Village credit goals.